2022
DOI: 10.3390/ijms232112753
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Transferrin in Experimental Glaucoma Models

Abstract: Iron is essential for retinal metabolism, but an excess of ferrous iron causes oxidative stress. In glaucomatous eyes, retinal ganglion cell (RGC) death has been associated with dysregulation of iron homeostasis. Transferrin (TF) is an endogenous iron transporter that controls ocular iron levels. Intraocular administration of TF is neuroprotective in various models of retinal degeneration, preventing iron overload and reducing iron-induced oxidative stress. Herein, we assessed the protective effects of TF on R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…A recent article includes all publications measuring iron indicators in the serum, aqueous humor, and tears of patients with glaucoma and in the retinal tissue layers of primates. 21 In addition to studies reporting increased ferritin and transferrin levels in the retinas of monkeys with glaucoma and humans with glaucoma, 22,23 there are several studies reporting increased levels of transferrin in the aqueous humors of people with PAAG, 24 and increased iron levels in the tears of people with glaucoma. 25 Also, when human aqueous humor iron levels were examined, it was determined that they were low in pseudo-exfoliating glaucoma and high in POAG.…”
Section: Discussionmentioning
confidence: 99%
“…A recent article includes all publications measuring iron indicators in the serum, aqueous humor, and tears of patients with glaucoma and in the retinal tissue layers of primates. 21 In addition to studies reporting increased ferritin and transferrin levels in the retinas of monkeys with glaucoma and humans with glaucoma, 22,23 there are several studies reporting increased levels of transferrin in the aqueous humors of people with PAAG, 24 and increased iron levels in the tears of people with glaucoma. 25 Also, when human aqueous humor iron levels were examined, it was determined that they were low in pseudo-exfoliating glaucoma and high in POAG.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with healthy individuals, glaucoma patients have a different distribution of iron in the retina, with iron overload around Müller cells, RGCs, and optic nerve axons and reduced iron in cones. 54 In the retina of glaucoma patients and monkeys, the mRNA and protein expression levels of iron regulatory proteins Tf, Cp and Ft were increased. 55 Iron metabolism plays an important role in the pathogenesis of glaucomatous neuropathy through cell death, oxidative stress, inflammation, mitochondrial dysfunction, and gene mutations.…”
Section: Main Textmentioning
confidence: 99%
“… 60 Tf can interfere with different cell death mechanisms such as apoptosis and iron death in the pathogenesis of glaucoma and has a protective effect on RGCs exposed to ocular hypertension. 54 …”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Transferrin is an iron transfer protein in the body, and studies have shown that transferrin receptors on retinal pigment epithelial cells are upregulated in diseases of the eye’s posterior segment, such as vitreoretinopathy, glaucomatous neuropathy, and age-related macular degeneration. As a result, retinal-targeted drug delivery using the reaction between the transferrin receptor and transferrin present on the cell surface is being studied [ 118 , 119 , 120 , 121 ]. When transferrin binds to its receptor on the cell surface, the complex containing transferrin is internalized and can easily enter the cell.…”
Section: Recent Progress and Challenges In Overcoming Biological Barr...mentioning
confidence: 99%